Pendampingan Gerakan Aksi Pungut Sampah Melalui Kuliah Kerja Nyata Tematik di Negeri Amahusu - Tahapary, Ghizella S.; Prafitri, Resky; Dumalang, Fienkan L (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The Waste Collection Action Movement is to achieve various positive things in terms of the environment, Public Health, cleanliness and sustainability. The garbage collection action movement was carried out with the aim of finding out existing information as well as knowledge about solutions in managing the polluted environment, especially the waste problem that always exists, and providing understanding to the local community in creating mutual concern for the environment. This garbage collection action movement was carried out at one of the locations of the Amahusu State Meeting Building Beach, because waste is the main problem that has not been completely handled in the Land of Amahusu. The implementation of the program is carried out through observation, socialization, preparation and design, socialization methods, social actions to collect garbage. The result of the beach cleanup action movement carried out by Real Work Lecture Students in the Land of Amahusu, is that first, this activity can change the lifestyle of the local community. Second, during the activity, the amount of waste that was successfully collected was as many as 26 garbage bags consisting of mixed waste, plastic waste, and glass bottle waste. Third, habits that are always fostered will result in concern for the environment in overcoming environmental problems, especially the waste problem in the Land of Amahusu